Divergent thinking of students in the field of education at a university in Lima - Balabarca Poves, Gabriela Amanda (2020)
The search to favor the development of creative thinking in students is an arduous and complex task that guides the possibility of implementing and operating it. Therefore, the objective of this research was to describe the levels of divergent thinking of students in the specialty of education at a university in Lima. The study was of a quantitative, descriptive level and non-experimental design approach. The population was made up of 200 students. An instrument was developed and applied to measure emergent thinking, validated and reliable (Cronbach's Alpha =, 894). It was determined that 61% have an average level of divergent thinking, with originality being predominant (β =, 407). It is concluded that, to improve their level of divergent thinking, they must be flexible about thinking and originality.